Gamification to Increase Interest in Learning Mathematics - Rojabi, Muhammad Afdan; Wang, Gunawan (Jurnal Pembelajaran Inovatif, 2024)
This study explores the effectiveness of gamification in mathematics learning using the Quizizz platform. The study involved 20 sixth-grade students at MIS Wahdatul Ikhwan Bogor and employed an experimental method with a pretest-posttest design. The analysis results showed a significant improvement in students' learning outcomes after the implementation of gamification. The use of Quizizz not only enhanced students' understanding and performance but also increased their motivation to learn and reduced boredom. The paired sample t-test showed a significance value of 0.000, indicating a significant difference between pretest and posttest scores. These findings suggest that gamification is an effective approach to improving students' learning outcomes and engagement in the mathematics learning process. Teachers are highly encouraged to integrate gamification into their teaching methods to create a more engaging and effective learning experience.